SPATIAL INEQUALITIES IN THE PROVISION OF PRIVATE HEALTH FACILITIES IN OYO STATE - Olaniyan Femi Abiodun (Faculty of Geography, Universitas Gadjah Mada, 2013)
This paper examines the spatial pattern of the provision of private health facilities and whatthe pattern portends for health needs in an era of global warming using the 33 LocalGovernment Areas of Oyo State as spatial units of analysis. The data used for this study werecollected from Oyo State Hospital Management Board and the National PopulationCommission. The findings of the study generally show that there are enormous spatialinequalities in the provision of private health facilities in the study area. Gini Coefficient andthe associated Lorenz Curve confirm that there is generally an unequal distribution of privatehealth facilities in the study area. The curve suggests that the most vulnerable segment of thepopulation to the health consequences of global warming are precluded from utilizing privatehealth facilities. Oyo state’s experience thus shows that there is need for policy measuresthat will ensure unrestricted access to health facilities in an era of global warming.